The Effect Murottal of Quran Therapy and Benson Relaxation on Anxiety Level of High-Risk Pregnancy - Anida Izatul Islami; Dede Gantini; Endang Astiriyani (JURNAL KEBIDANAN, 2020)
Pregnancy can be in a high-risk category, which is grouped according to Poedji Rochjati Scoring Card that causes anxiety. Anxiety in a pregnant woman can trigger contractions, abortus, increasing blood pressure that can trigger the occurrence of preeclampsia, etc. One of the therapies to deal with anxiety is murottal of Quran therapy and Benson relaxation. Murottal of Quran therapy is a complementary therapy that is applied by listening to the passage of Ar Rahman letter, whereas, Benson relaxation is a complementary therapy that is done by guiding clients to unite beliefs and regulate breathing. Both therapies have a relaxing effect, which can reduce stress and anxiety. The purpose of this research is to know the influence of therapeutic murottal Quran and Benson relaxation on pregnancy anxiety high-risk. This research use Quasy experimental design with the design of two group pretests and a posttest involving 39 respondents with the criteria of high-risk expectant mothers experiencing anxiety in Kelurahan Setiawargi Kecamatan Tamansari Tasikmlaya City. The analysis of data in this study used quantitative analysis by describing the characteristics of each research variable and assessing the influence of therapy Murottal Quran and Benson relaxation of high risk expectant pregnant mothers using paired T-test samples. The result of this study was obtained that the anxiety of pregnant mothers high-risk decreased after intervention in each group. Based on the explanation above, it can be concluded that there is a therapeutic influence of  murottal Quran and Benson relaxation to the anxiety of high-risk expectant mothers.